Compatibility of Work and Family Life of Employees in the Healthcare Sector: An Issue in Health Services Research - Lukasczik, Matthias; Ahnert, Jutta; Stroebl, Veronika; Vogel, Heiner; Donath, Carolin; Enger, Ilka; Grässel, Elmar; Heyelmann, Lena; Lux, Heidemarie; Maurer, Jochen; Özbe, Dominik; Spieckenbaum, Stefanie; et al. (Gesundheitswesen, 2018)
BACKGROUND: Healthcare professionals are confronted with specific work-related demands that influence work-family relations and might indirectly affect the quality of healthcare. This paper seeks to provide an overview of the current state of research on this topic of relevance to health services research. The overview may serve as a starting point for modifying structures in the healthcare system (especially in rural regions) with the aim of improving work-family compatibility. METHODS: A systematic national and international literature search was conducted in terms of a scoping review. The following criteria/contents to be covered in publications were defined: work-family compatibility; work-family interface and work-family conflict in employees working in healthcare; healthcare professions in rural areas and links with work-family issues; interventions to improve work-family compatibility. 145 publications were included in the overview. RESULTS: The available literature focuses on physicians and nursing staff while publications on other professions are largely lacking. The methodological quality of existing studies is mostly low, including a lack of meta-analyses. Several studies document dissatisfaction in physicians and nursing staff regarding reconciliation of work and family life. Only few intervention studies were found that seek to improve work-life compatibility; few of them focus on employees in healthcare. There are also deficits with respect to linking work-family issues with aspects of healthcare in rural areas. CONCLUSIONS: There is a shortage of systematic national and international research regarding work-family compatibility, especially when it comes to the evaluation of interventions. The overview provides starting points for improving work-family compatibility in healthcare.
EVALuna2:211666